PENGARUH BUDAYA KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH PASAMAN BARAT - Edi Warman (JURNAL PUNDI, 2020)
Fast traslate Icon translate Employee performance is important to be considered by every organization because human beings, in this case employees are the main factors in the work process which in turn will make the overall performance of agencies take place properly. Performance can be seen from the achievements in achieving a certain target with a certain time. This study aims to examine the impact of the impact of work culture and work discipline on employee performance in the West Pasaman regional development planning office. The sampling technique used was saturated sample technique which is 60 respondents. Data collection techniques in this study were questionnaires. The analysis method is a multiple analysis method with the help of the SPSS application. The initial test is tested for validity to test the accuracy of the instrument being measured. With the results of the study indicate that work culture has a positive and significant effect on employee performance and work discipline has a positive and significant effect on employee performance.